Differences in clinical features of acute exacerbation between connective tissue disease-associated interstitial pneumonia and idiopathic pulmonary fibrosis - Enomoto, Noriyuki (Chron Respir Dis, 2018)
Acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF) is a devastating condition that frequently occurs in the advanced stage of IPF. However, the clinical features in AE of connective tissue disease-associated interstitial pneumonia (AE-CTD-IP) have not been well-established. The aim of this study was to clarify the clinical features of AE-CTD-IP and to compare them with those of AE-IPF. Fifteen AE-CTD-IP patients and 48 AE-IPF patients who were diagnosed and treated at our hospital were retrospectively studied. Compared with AE-IPF patients, AE-CTD-IP patients had a significantly higher %FVC (median, 94.8 vs. 56.3%; p < 0.001) and a lower extent of honeycombing on HRCT (p = 0.020) within 1 year before AE. At AE, AE-CTD-IP patients showed higher white blood cell counts (12.0 vs. 9.9 × 10(3)/μL; p = 0.023), higher CRP (10.2 vs. 6.7 mg/dL; p = 0.027), and longer period from admission to the beginning of AE treatment (4 vs. 1 days; p = 0.003) than AE-IPF patients. In addition, patients with AE-CTD-IP had poor prognosis as in those with AE-IPF (log-rank; p = 0.171). In conclusion, AE-CTD-IP occurred even in the early stage of IP and had more inflammatory status than in AE-IPF.